Fatalism and Truth at a Time - Marxen, Chad (Stance: an international undergraduate philosophy journal, 2013)
In this paper, I will examine an argument for fatalism. I will offer a formalized version of the argument and analyze one of the argument’s most controversial assumptions. Then, I will argue that one ought to reject the assumption that propositions about the future are true facts of the past, even if no one makes reference to such propositions.